Perlindungan Hukum Pekerja Digital Freelance di Era Platform Economy: Analisis Gap Regulasi Ketenagakerjaan dan Rekomendasi Reformasi Normatif - Sari, Tika; Indah, Nara; Sintia, Putri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The development of the platform economy has given rise to new employment models that blur the boundaries between formal employment relationships and independent partnerships. Freelance digital workers, who rely on digital platforms as intermediaries, face systemic vulnerabilities due to normative gaps within Indonesia’s labor law framework. This study aims to analyze regulatory gaps in the protection of freelance digital workers under the normative framework of the Manpower Law No. 13 of 2003 and the Job Creation Law No. 6 of 2023, to identify elements of employment relationships that are factually fulfilled despite lacking legal recognition, and to formulate cohesive reform recommendations. Using a normative juridical approach with doctrinal analysis, this study finds that: (1) freelance digital workers factually fulfill the elements of an employment relationship (work, wages, and control) through algorithmic mechanisms, despite being contractually constructed as “partners”; (2) economic dependence and algorithmic control create a form of digital subordination that is not recognized by existing regulations; (3) current regulations do not explicitly accommodate protections related to social security, minimum wages, and algorithmic transparency; and (4) dispute resolution mechanisms remain unclear, leaving workers in a highly vulnerable position. The recommendations include: legal recognition of platform workers as a distinct employment category, the imposition of minimum social security obligations, regulation of algorithmic transparency, and the establishment of fair dispute resolution mechanisms. These reforms are essential to ensure social justice and worker welfare in the digital economy era, in line with the mandate of Constitutional Court Decision No. 168/PUU-XXI/2023.